Dedicated team to ambulatory care for patients with COVID-19 requiring oxygen: Low rate of hospital readmission. (October 2022) - Viel, Sophie; Markowicz, Samuel; Ait-Medjber, Larbi; Ouissa, Rachida; Delta, Delphine; Portecop, Patrick; Foucan, Tania; Roger, Pierre-Marie
Highlights: No study reported ambulatory care for patients with COVID-19 requiring oxygen. We dedicated a medical team to this task before any hospital stay. Dedicated a medical team led to a low rate of hospital readmission compared with the usual management. The dedicated a medical team systematically prescribed steroids and anticoagulation prevention. Abstract: Objectives: We aimed to determine the impact of a dedicated medical team (DMT) on ambulatory care for patients requiring oxygen. Methods: The DMT selected patients requiring oxygen for less than 5 l/min in the emergency department (ED). The rate of ED readmission was compared in patients managed by the DMT and those managed by the ED physicians (EDPs). Consensual treatment for COVID-19 pneumonia with oxygen requirement was steroids + preventive anticoagulation. Results: A total of 1397 patients with COVID-19 came to our ED from the first to the 31 st of August, 2021, among whom 580 (41%) had ambulatory care. A total of 82 (14.1%) patients were managed by the DMT, with a rate of ED readmission of 4.8% (4/82), compared with 13.6% (68/498) for those managed by EDPs ( P <0.001). Focusing on the 45/498 (9.0%) patients requiring oxygen and managed by EDPs, the rate of ED readmission was 20%, P = 0.017. Prescription of the consensual treatment concerned 96% versus 40% for those patients requiring oxygen for the DMT and the EDP, respectively ( P <0.001). Conclusion: A DMT for ambulatory care of patients with COVID-19 requiring oxygen was associated with less return to the ED than usual practices.